Upaya Penurunan Tingkat Turnover Karyawan Project PT. X - Shania Paramitha Kusuma; Herri Christian Palit (Jurnal Titra, 2021)
PT X is one of fast moving consumer goods company in the tobacco industry. Since 2018, PT X has started to launch new product (project launching) in various city in Indonesia. This projects have given impact for several department, including recruitment department for employee fulfilment. Fulfilment process was difficult to do because turnover rate was more than 40%. Pareto’s result shows three main reasons that influence employee to leave the company. The reasons are disciplinary action, unclear status and benefit, and performance issue. The root causes of the three main reasons are identified by 5 whys analysis and analysis of employee characteristics through Cramer’s V test and crosstab. Based of analysis, the root causes are the company didn’t have job description, employees don’t have many experiences, training just is given in the beginning of project and unequal, the company doesn’t have a clear appraisal for employee performance, engagement rate is low and there isn’t salary invoice. Based on the root causes of employee turnover, the solutions that can offer are making job description and spesification, making training guidelines, implementing 360° assessments, giving rewards and giving salary invoice. Five solutions are expected to reduce employee turnover rate of employee project PT X.